2016
DOI: 10.14737/journal.aavs/2016/4.8.441.448
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Contamination Estimates of Mycobacterium Avium Subspecies Paratuberculosis in Fresh Cottage Cheese (Paneer) Sold in Rural, Semi-Urban and Peri-Urban Regions of South Uttar Pradesh using Multiple Diagnostic Tests

Abstract: Paneer (fresh cottage cheese) samples collected from local dairy shops in rural (Farah), peri-urban and urban (Mathura and Agra) regions of South Uttar Pradesh were screened by six tests combinations to estimate the rate of 'bio-contamination' and 'bio-typing' of MAP (paraTB bacilli). Of 55 paneer samples screened, 54.5, 32.7, 54.5, 74.5, 50.9 and 63.6% were positive by microscopy, IS900 PCR, indigenous ELISA kit, Dot-ELISA, Latex Agglutination test and indirect Fluorescent Antibody tests, respectively. Except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
0
1
Order By: Relevance
“…Contrarily, Bhutediya et al, (2017) et al, 2012). The present study also disagrees with several workers who have reported the detection of MAP in commercial milk and milk products of India (Stephen et al, 2016;Raghuvanshi et al, 2013). The i_ELISA of milk sample was found to be most sensitive compared to microscopy, IS900 PCR and Rt-PCR in this study.…”
Section: Resultscontrasting
confidence: 99%
“…Contrarily, Bhutediya et al, (2017) et al, 2012). The present study also disagrees with several workers who have reported the detection of MAP in commercial milk and milk products of India (Stephen et al, 2016;Raghuvanshi et al, 2013). The i_ELISA of milk sample was found to be most sensitive compared to microscopy, IS900 PCR and Rt-PCR in this study.…”
Section: Resultscontrasting
confidence: 99%